2007
DOI: 10.1093/jmedent/44.6.1067
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus-Infected Dead Corvids Increase the Risk of Infection inCulexMosquitoes (Diptera: Culicidae) in Domestic Landscapes

Abstract: A comparative study of West Nile virus (family Flaviviridae, genus Flavivirus, WNV) infection rates in Culex mosquitoes collected at 13 sites, seven reporting WNV-positive dead corvids (case sites) and six without reported dead birds (control sites) was conducted in Davis, CA, from 14 to 21 July at the beginning of the 2006 WNV outbreak. In total, 3,051 Culex mosquitoes were collected using gravid traps and CO 2 -baited traps; WNV-infected mosquitoes were only collected with CO 2 -baited traps. WNV-infected Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Mosquito risk was found to be statistically significantly related to annual WNV-infected dead birds sentinel data, averaged for the 2004–2010 ( Kala et al, 2017 ). Annual WNV-infected dead birds sentinel data has been shown to be useful for estimating human WNV risk by multiple studies ( Eidson et al, 2001a , 2001b , 2001c ; Guptill et al, 2003 ; Mostashari et al, 2003 ; Ruiz et al, 2004 ; Johnson et al, 2006 ; Nielsen & Reisen, 2007 ; Patnaik, Juliusson & Vogt, 2007 ; Chaintoutis et al, 2014 ). The mosquito risk model resulted in a risk surface with a range of 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…Mosquito risk was found to be statistically significantly related to annual WNV-infected dead birds sentinel data, averaged for the 2004–2010 ( Kala et al, 2017 ). Annual WNV-infected dead birds sentinel data has been shown to be useful for estimating human WNV risk by multiple studies ( Eidson et al, 2001a , 2001b , 2001c ; Guptill et al, 2003 ; Mostashari et al, 2003 ; Ruiz et al, 2004 ; Johnson et al, 2006 ; Nielsen & Reisen, 2007 ; Patnaik, Juliusson & Vogt, 2007 ; Chaintoutis et al, 2014 ). The mosquito risk model resulted in a risk surface with a range of 0 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…We used data on WNV-positive corvid (i.e., blue jays and American crows) carcasses only, as a consequence of their high WNV mortality and proximity to humans (Nielsen and Reisen 2007). We divided the number of WNV-positive corvid carcasses per census tract by the 2000 population estimate (U.S.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, our objectives were to describe and quantify the spatial distribution of mosquito abundance and WNV infection in mosquitoes, humans, and birds, specifically corvids (blue jays and American crows), that are considered sentinels of local virus activity (Nielsen and Reisen 2007) in the city of Atlanta, Georgia, from 2001–2007 and to assess the relationship between CSO-affected streams and WNV infection.…”
mentioning
confidence: 99%
“…Although it could be concluded that this resultant reduction of the breeding population would diminish transmission, high avian mortality is postulated to potentially increase transmission in three ways: (i) survival of previously infected and now immune birds could dilute the effect of subsequent transmission events [50], (ii) mortality in birds is associated with high peripheral viremia leading to the efficient infection of moderately susceptible mosquito vectors [23, 77, 83], and (iii) increased pathological manifestations could favor increased infection of mosquitoes due to reduced anti-mosquito defensive behavior of moribund avian hosts [33] as well as increased attractiveness to mosquitoes as a result of hyperthermia [77]. The time period in which avian hosts such as AMCR are the most viremic coincides with maximal viremia and moribund birds, presenting with elevated viremias on the ground could result in increased efficiency for infectivity of contact with vector mosquitoes, thereby increasing transmission potential of WNV to humans or equines [108]. Furthermore, it has been hypothesized that vector-borne agents have the potential for tolerance of higher levels of mortality.…”
Section: Factors Associated With West Nile Viral Emergencementioning
confidence: 99%